Crisis management: A bibliometric analysis - Syadiyah Abdul Shukor; Norasikin Salikin; Ummi Salwa Ahmad Bustamam; Intan Fatimah Anwar; Siti Nurulhuda Nordin (USIM Press, 2024)
Journal of Muamalat and Islamic Finance Research Vol. 20, Page (64-78)